Analysis of verbal interaction in teaching theoretical and practical subjects in the Department of Art Education / College of Fine Arts / University of Babylon (Journal of the College of Basic Education, 2022)
The verbal interaction is a direct input to the evaluation through which the teacher's behavior is monitored in an organized manner during classroom teaching using various recording methods. Teaching, in essence, is an interaction process that depends on the exchange of language between the teacher and his students, both verbally and visually, in order for the teacher to be more able to analyze educational situations and be more accurate. In defining the goals of his lesson and achieving them in a proper classroom atmosphere, he needs training in analyzing verbal and non-verbal interaction systems that suit him, allowing him to better understand and evaluate artistic activities, in which he is most of the time an important and effective element.